2017
DOI: 10.2196/mhealth.8228
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of SmartMoms, a Novel eHealth Intervention for Management of Gestational Weight Gain: Randomized Controlled Pilot Trial

Abstract: BackgroundTwo-thirds of pregnant women exceed gestational weight gain (GWG) recommendations. Because excess GWG is associated with adverse outcomes for mother and child, development of scalable and cost-effective approaches to deliver intensive lifestyle programs during pregnancy is urgent.ObjectiveThe aim of this study was to decrease the proportion of women who exceed the Institute of Medicine (IOM) 2009 GWG guidelines.MethodsIn a parallel-arm randomized controlled trial, 54 pregnant women (age 18-40 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 18 publications
5
88
0
Order By: Relevance
“…e specific uses of mobile apps through the studies were diverse. e Expecting Success study reported in a previous paper [55] that the SmartMoms remote intervention group received a Fitbit device accompanied by its app to selfmonitor body weight and step counts daily. It must be pointed out that SmartMoms intervention was designed to assist an expectant mother in gaining weight within the recommended guidelines.…”
Section: Not Applicablementioning
confidence: 99%
“…e specific uses of mobile apps through the studies were diverse. e Expecting Success study reported in a previous paper [55] that the SmartMoms remote intervention group received a Fitbit device accompanied by its app to selfmonitor body weight and step counts daily. It must be pointed out that SmartMoms intervention was designed to assist an expectant mother in gaining weight within the recommended guidelines.…”
Section: Not Applicablementioning
confidence: 99%
“…Indeed, WIC participants most often only receive two contacts (more if breastfeeding). Combining government resources including universal participant data records for easy transmittal of health information between the entities allows for a continuity of care and implementation of more efficient and effective (32,52). b (4) At each WIC visit, measure weight and plot on a weight gain or weight loss chart showing an ideal weight zone.…”
Section: Implications For Practice And/or Policymentioning
confidence: 99%
“…Therefore, granting public access to seemingly valuable information is not an efficient way to increase awareness of health risks or to support individuals in making healthy choices. Thus it is not surprising that one of the principal aims of eHealth studies is assessing the actual response to the delivered information [6,13].…”
Section: Health Education and Promotionmentioning
confidence: 99%
“…In this field, telemedicine became an accepted solution which facilitates the healthcare process while keeping cost under control. There are numerous examples of successful implementations of such projects [6,9,16,20]. Parallel to their achievements, there is a constant need to evaluate the new solutions.…”
Section: Treatment and Rehabilitationmentioning
confidence: 99%